A infância pelas vozes e gestos das crianças na EMEI Eufrázia Pengo Lorensi, Santa Maria/RS - Heck, Márcia Fernanda (2024)
This Master’s Dissertation of the Postgraduate Program in Education of the Federal University of Santa Maria is linked to the Research Line 2: Educational Public Policies, Educational Practices and their Interfaces and has as its theme “childhoods, educational practices in early childhood education in EMEI Eufrázia Pengo Lorensi and its potential”. The research problem questions how educational practices have children as the center of the pedagogical process in order to ensure their protagonism. And its main objective is to analyze how educational practices in early childhood education consider children and their protagonism as the center of the pedagogical process, having their own languages and expressions as elements of analysis. Seeking to achieve the general objective, the research goes through three specific objectives: 1) to recognize the presence of the concepts of childhood and child in public policies for early childhood education and its alignment with the documentation of EMEI Eufrázia Pengo Lorensi; 2) identify if there is a role of children during educational practices in EMEI Eufrázia Pengo Lorensi; 3) analyze how children re-signify the spaces designed and organized by the teacher for the development of educational practices. The research is, therefore, narrative, qualitative, ethnographic and with children (CORSARO, 2009, 2011), in an exercise of listening, seeing and interpreting the voices and gestures of the children of the pre-school class B, afternoon shift, to make children visible. The data were produced through observation and listening, dense description in field diary, photographic and filmic records, considering the ethical aspects of research with children, according to Barbosa (2014). To permeate the reflections and discussions, we seek to dialogue with the field of sociology of childhood from Corsaro (2009), Christensen and James (2005), childhood pedagogy from Barbosa (2007, 2009, 2014), Faria (2005, 2011), Martins Filho (2020), Rinaldi (2020), Fortunati (2014), among others and others. It is expected that the research will make it possible to discuss about the policies for Early Childhood Education, especially from its documentation, and possibly enable the construction of new looks and reflections on educational practices in Early Childhood Education, the appreciation of children’s cultures and the role of children in the school environment.